An Investigation into the Horizon of “Preliminary Norms in Translation”: Denominations of Works in Italian to Ottoman Turkish in M. Rauf’s “İtalyan Tarih-i Edebiyatı” (History of Italian Literature) - Eshabil Bozkurt; Deniz Dilşad Karail Nazlıcan (İstanbul Üniversitesi Çeviribilim Dergisi)
This article aims to examine the translations into Ottoman Turkish of Italian literary work titles found in a book titled “İtalyan Tarih-i Edebiyatı”, the first work on the history of Italian literature in the Turkish cultural literary system. In this study, M. Rauf divided Italian literature into four periods. Additionally, he provides information about some poets and writers he deems important, translating brief excerpts from their works into Ottoman Turkish, and sometimes only providing the names of the authors, poets, and their works. In this article, the Italian work titles mentioned in M. Rauf’s book and their translations/adaptations to Ottoman Turkish are examined. The theoretical framework of the study is based on Gideon Toury’s “preliminary norms.” Toury, who categorises translation norms into two groups as “preliminary norms” and “operational norms,” also discusses “initial norms.” The decisions made by the translator prior to the translation process, such as the reasons for selecting a particular author and work for translation, whether the translation is conducted directly from the original source language or through an intermediary language, and if an intermediary language is used, which language it is, constitute the “preliminary norms.” With the use of this methodological approach in this contribution, it is intended to analyse exhaustively and accurately the translations and/or adaptations into Ottoman Turkish of the titles of Italian literary works present in M. Rauf’s book “İtalyan Tarih-i Edebiyatı,” thus providing a significant perspective on the reception and understanding of Italian literature in the Ottoman Turkish cultural universe of the period.